Mechanisms for the interactions between acidic oils and surfactant enhanced alkaline solutions. - Touhami, Youssef. (University of Ottawa (Canada), 1996)
The reduction of interfacial tension between acidic oils and floodwater is one of the most important mechanisms of improved oil recovery. The predominant oil recovery techniques are micellar and alkaline flooding. In such processes, surfactant is adsorbed at the oil-water interface and thus reduces the interfacial tension creating conditions for oil mobilization a displacement. In the micellar process, commercial surfactants are injected along with the aqueous phase, while in the alkaline process surfactants are produced in situ by a reaction between acids in the oil and the injected alkaline reagents. A precise and accurate method for monitoring and measuring both equilibrium and transient interfacial tension is required to help to develop an understanding of the mechanisms that govern the interactions of acidic oils with alkaline reagents. For this purpose, an apparatus has been set up based upon the drop shape method for the determination of surface and interfacial tension. An interfacial activity model has been proposed to predict the equilibrium interfacial tension behavior of acidic oil/surfactant enhanced alkaline systems. The model accounts for a mixed interfacial layer and mixed micelle formation by the un-ionized acid, ionized acid and added surfactant. A mass action model is adopted for the formation of micelles in conjunction with an empirical relationship for the change in the critical micelle concentration. The agreement between model predictions and experiments is satisfactory and confirms the mechanisms proposed. For the acidic oil/alkali system, it has been found that un-ionized acid adsorbs onto the interface along with ionized acid resulting in lower interfacial tension, but fails to produce ultra low values because the ionic strength is not constant as the pH varies. Also it has been found that the acid lowers the interfacial tension of the oil/added surfactant systems by simultaneously adsorbing onto the interface, and reducing the critical micelle concentration of the added surfactant. A mechanistic interpretation of the transient interfacial tension behavior arising from the interactions between acidic oil and surfactant-alkaline systems is developed. A physico-chemical model based on Nernstian theory of convective diffusion, Langmuirian theory of interfacial sorption kinetics, and electrical interfacial phenomena has been invoked to account for the transient nature of the interfacial tension. The results show that the interfacial tension arising from the interaction of these chemical combinations with model acidic oil exhibits a marked transient behavior. The magnitude of interfacial tension variations changes not only with alkali concentration but also with surfactant concentration. The pertinent sorptive rate constants that characterize transient behavior are precisely estimated by correlating experimental interfacial tension data with the proposed model. A very good overall agreement is obtained between the experimental values and those predicted by the model. A better model of the interactions between acidic oil and alkaline solutions has been developed. The improvement is mainly related to an enhanced measurement technique, modification of the adsorption isotherms as well as the kinetic equations. These changes allow for the co-adsorption of the un-ionized acid along with the ionized acid at the interface. The extension of the acidic oil/alkaline model to incorporate an additional pre-formed surfactant is also accomplished by a modification of the adsorption isotherms, of the micellar relationship and of the resulting equilibria. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.